A small ubiquitin-related polypeptide involved in targeting RanGAP1 to nuclear pore complex protein RanBP2 - Mahajan, Rohit; Delphin, Christian; Guan, Tinglu; Gerace, Larry; Melchior, Frauke (Cell, 1997)
We have found that the mammalian Ran GTPase-activating protein RanGAP1 is highly concentrated at the cytoplasmic periphery of the nuclear pore complex (NPC), where it associates with the 358-kDa Ran-GTP-binding protein RanBP2. This interaction requires the ATP-dependent posttranslational conjugation of RanGAP1 with SUMO-1 (for small ubiquitin-related modifier), a novel protein of 101 amino acids that contains low but significant homology to ubiquitin. SUMO-1 appears to represent the prototype for a novel family of ubiquitin-related protein modifiers. Inhibition of nuclear protein import resulting from antibodies directed at NPC-associated RanGAP1 cannot be overcome by soluble cytosolic RanGAP1, indicating that GTP hydrolysis by Ran at RanBP2 is required for nuclear protein import.
Gesehen am 13.03.2023